Family policies' long-term effects on poverty: a comparative analysis of single and partnered mothers - Hannah Zagel; Wim Van Lancker (Journal of European Social Policy, 2022)
This study investigates whether generous family policies at the transition to parenthood reduce single and partnered mothers' economic disadvantages later in the life course. Previous research usually focused on the immediate effects of family policies and disregards potential longer-term effects. In this study, we suggest taking a life-course perspective to study the relationships between family policy and mothers' poverty risks. We empirically investigate how investment in child benefits, childcare services and parental leave measures at the transition to parenthood are associated with poverty outcomes at later life stages and whether these associations hold over time. We draw on pooled EU-SILC data, and an original policy dataset based on OECD expenditure data for child benefits, childcare and parental leave from 1994 to 2015. We find that mothers' observed increase in poverty over time is slower in countries with high levels of spending for childcare at the transition to parenthood than in lower spending countries. The gap between partnered and single mothers was also diminishing in contexts of high childcare expenditure. For the other two policies, we did not find these links. These results do lend support to the claim that childcare is a prime example of a social investment policy with returns later in the life course and represents a life-course policy that seems to be able to disrupt economic path dependencies. The results for the other two policies suggest, however, a limited potential of family policy spending at transition to parenthood to reduce the poverty gap between partnered and single mothers over the course of life.
doi:10.25384/SAGE.18093481.v1
Keywords: 320; family policy; life course; single mothers; childcare; EU-SILC; poverty; social expenditures